Type Iax supernovae as a few-parameter family - Barna, Barnabás; Kromer, Markus (Monthly notices of the Royal Astronomical Society, 2018)
We present the direct spectroscopic modelling of five Type Iax supernovae (SNe) with the 1D Monte Carlo radiative transfer code tardis. The abundance tomography technique is used to map the chemical structure and physical properties of the SN atmospheres. By fitting multiple spectral epochs with self-consistent ejecta models, we can constrain the location of some elements within the ejecta. The synthetic spectra of the best-fitting models can reproduce the flux continuum and the main absorption features in the whole sample. We find that the mass fractions of iron-group elements and intermediate-mass elements show a decreasing trend towards the outer regions of the atmospheres when we use density profiles similar to those of deflagration models in the literature. Oxygen is the only element that could be dominant at higher velocities. The stratified abundance structure contradicts the well-mixed chemical profiles predicted by pure deflagration models. Based on the derived densities and abundances, a template model atmosphere is created for the SN Iax class and compared with the observed spectra. The free parameters are the scaling of the density profile, the velocity shift of the abundance template, and the peak luminosity. The results of this research support the idea that all SNe Iax can be described by a similar internal structure, which argues for a common origin of this class of explosions.
Gesehen am 05.03.2020